PRESENTATION OF THE POLITICAL LEADERS’ PERSONALITIES ON TV NEWS: THE CASE IS TURKEY PRESIDENTAL ELECTIONS IN 2014 - Çelikiz, Ekrem (PEOPLE: International Journal of Social Sciences, 2018)
Political parties during the election period in Turkey, they use mass media effectively in their propaganda activities. Television is one of the widely used mass media during the election period in Turkey. In this study, in 2014 the presidential elections in Turkey; it has been tried to determine whether a special presentation has been made in television news bulletins related to the personalities of political candidates .In the news texts, Mccrea and Costa's Five Factor Personality Theory is based on personality qualifications in order to determine whether there are adjectives used in relation to the personalities of political candidates. This work has been researched that "The same political candidates are presenting different audiences on different TV channels" hypothesis. How are the personalities of political leaders presented in television news bulletins? What extent are the personality characteristics of political candidates reflected to news texts in TV news bulletins? that questions will be searched for an answer in this study. The discourse analysis method will be taken as a bases of the study. As a result of the study, news bulletins on different TV channels showed that the same political candidate was presented with different personality qualifications. Also, it can be said that TV channels that have to be neutral, violate the principles of neutrality through personality qualifications in news bulletins.